Some Aspects of Voice User Interfaces Development for Internet And Computer Control Applications - Maskeliunas, R.; Ratkevicius, K.; Rudzionis, V. (Elektronika ir Elektrotechnika, 2013)
This paper deals with some aspects of development voice user interfaces for several applications. The realistic scenario when developing VUI for such languages as Lithuanian is adaptation of foreign language speech recognizer. But not all voice commands could be recognized successfully enough using adapted recognizer. Hence the importance to implement hybrid recognizer arises. Several practical applications using Lithuanian voice command recognitions are presented. The experimental investigation showed that 90 percent recognition accuracy was achieved in average using adaptation of foreign language speech engine. Detailed analysis showed that most commands are recognized with very high accuracy. For those commands that aren’t recognized accurately enough hybrid recognition principle may be applied. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3469